2015
DOI: 10.1096/fj.14-269225
|View full text |Cite
|
Sign up to set email alerts
|

Novel cell‐penetrating peptide targeting mitochondria

Abstract: Cell-penetrating peptides (CPPs) are short, nontoxic peptides with cationic and/or amphipathic properties able to cross the cellular membrane. CPPs are used for the delivery of a wide variety of cargoes, such as proteins, oligonucleotides, and therapeutic molecules. The aim of the present study was to synthesize unusually small novel CPPs targeting mitochondria based on the Szeto-Schiller peptide (SS-31) to influence intramitochondrial processes and to improve the biologic effects. All the peptides used were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 32 publications
(37 reference statements)
0
82
0
Order By: Relevance
“…The predominant approach for targeting CPP-bound cargo calls for the fusion of canonical signal sequences to cargo proteins, or even to the CPP tag itself (reviewed in (54)). Using this methodology, cargos have been delivered to the nucleus (55, 56), nucleolus (57), lysosome (58), peroxisome (55), the mitochondria (55, 59, 60) and the endoplasmic reticulum (55, 61), to name a few. Drawbacks to this approach include decreased uptake of tagged CPPs (61) and potential endosomal entrapment en route to the intended compartment.…”
Section: Busting Out: Escape From the Endosomementioning
confidence: 99%
“…The predominant approach for targeting CPP-bound cargo calls for the fusion of canonical signal sequences to cargo proteins, or even to the CPP tag itself (reviewed in (54)). Using this methodology, cargos have been delivered to the nucleus (55, 56), nucleolus (57), lysosome (58), peroxisome (55), the mitochondria (55, 59, 60) and the endoplasmic reticulum (55, 61), to name a few. Drawbacks to this approach include decreased uptake of tagged CPPs (61) and potential endosomal entrapment en route to the intended compartment.…”
Section: Busting Out: Escape From the Endosomementioning
confidence: 99%
“…We have previously shown that mtCPP1 and UPF25 did not affect the viability of different cell lines even at high concentration (100 μM) 27, 28. We compared the effects of mtgCPP at different concentrations on the viability of HeLa 705 cells after 24 hr (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…All peptides were designed based on our previously published peptides, mtCPP1 and UPF25 27, 28. Peptides were synthesized in stepwise manner in a 0.1 mmol scale on a Biotage Alstra Plus peptide synthesizer (Biotage) using a fluorenylmethyloxycarbonyl (fmoc) solid-phase peptide synthesis (SPPS) strategy with ChemMatrix Rink Amide resin (0.45 mmol/g) as a solid support to obtain C-terminally amidated peptides 30 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to neuronal cell surface receptor interactions, CARPs may also exert pleiotropic neuroprotective effects by targeting mitochondria and maintaining mitochondrial integrity by reducing calcium influx into the organelle [65,77,78,79,80,81,82,83]. CARPs have the capacity to inhibit proteolytic enzymes including the proteasome [84,85], as well as pro-protein convertases [86,87,88] that activate MMPs [89].…”
Section: Neuroprotective Peptides and Their Therapeutic Applicatiomentioning
confidence: 99%